EVIDENCE-BASED PRACTICE DALAM KONSELING: SEBUAH METODE PENGAMBILAN KEPUTUSAN UNTUK MENGHASILKAN PELAYANAN YANG EFEKTIF DAN EFISIEN - Haryadi, Rudi; Fauzi, Zainal (JURNAL KONSELING GUSJIGANG, 2017)
This article aims to examine the concept of evidence-based practice in counseling. In the last few decades, service-related professions, such as counseling, are finding new evidence-based practice trends (EBPs). The purpose of using EBP in counseling is to improve the effectiveness and efficiency of mental health services resulting in accountability to the public. The EBP decision-making process in counseling can be through five main stages: developing questions; collecting research results; reviewing evidences critically; select and implement eviden; and monitor progress of changes to clients. Implementation of this phase is a long process and requires the clinical expertise of the counselor in elaborating the collected research results, and the client's needs based on their characteristics, culture, and preferences. To this end, this article recommends the need for special training for counselors to implement evidence-based practice in counseling.